STRATEGI PERENCANAAN PEMBANGUNAN PARIWISATA KERTAGOSA DI KABUPATEN KLUNGKUNG - I Made Trisna Semara (Jurnal Ilmiah Hospitality Management, 2013)
The purpose of the research is to know the potential of tourism, the impact of tourism and tourism development planning strategy. The benefit of this research is to increase tourist arrivals and protectcultural heritage. The research use qualitative descriptive method and SWOTanalysis. The result of the research is Kertagosatourismhasgood potentialandfriendly.It supportsthe developmentof tourismin the future.Kertagosatourismpotentialcan be seenfromthe fivetypes ofsupplyowned. That can be seenfrom thetourist attraction, accessibility, amenities, ancillaries, andcommunityinvolvement. The development oftourismimproves quality of life, wellbeingandcommunity needs. Andalso, protect thehistoricalandculturalvaluefor Kertagosatourist destination.